Translating local binding energy to a device effective one. Issue 2 (26th November 2019) - Liraz, Dan; Cheng, Pei; Yang, Yang; Tessler, Nir
Abstract : While nonfullerene acceptors based organic photovoltaics reaching high power conversion efficiency, their binding energy is 150–500 meV. Here there is a model considering disorder and entropy that able to quantitatively explain this controversy. Abstract : One of the puzzles in the field of organic photovoltaic cells (OPVs) is the high exciton dissociation (charge generation) efficiency even though simple Coulomb based arguments would predict a binding energy of 150–500 meV that would suppress such dissociation. Not knowing which mechanism drives such high dissociation efficiency prevents researchers from establishing clear design rules. The common approach to solve this puzzle is to assume that the binding energy must be lower due to delocalization, disorder or entropy considerations. However, using these theories to quantitatively reproduce the dissociation is challenging. Here, considering entropy and disorder, a new approach is suggested using exciton dissociation efficiency as the parameter to weigh the effect of the energetic disorder. The effective entropy–disorder (EED) model predicts the device-equivalent charge generation efficiency, and provides a consistent new definition for the effective binding energy ( E b, eff ). For the first time, it is possible to directly compare a model with experimental results of a non-fullerene acceptor organic solar cell. Such comparison reveals that high dissociation efficiency does not require E b, eff lower than 100 meV and that high dissociation efficiency is driven by a combined effect of the energy landscape and a mobility that is significantly higher than the steady state one.